Diaper Dermatitis: Prevalence and Associated Factors in 2 University Daycare Centers - Porntipa Suebsarakam; Jitjira Chaiyarit; Leelawadee Techasatian (SAGE Publishing, 2020)
Purpose: Diaper dermatitis is uncommon in children older than 2 years because the majority of these children are diaper independent. However, diaper dermatitis still occurs, especially in children in daycare settings. This study attempted to determine the prevalence of diaper dermatitis and its associated factors among children aged 2 to 4 years attending daycare centers. Cross-sectional analysis and tests for correlation were conducted to determine the factors associated with diaper dermatitis among the study population. Results: The prevalence of diaper dermatitis during the study period was 17.2%. Factors significantly correlated with the occurrence of diaper dermatitis were beginning toilet training later than 2 years of age (odds ratio [OR] = 2.84, 95% CI = 1.17-6.86, P = .02) and the use of oral antibiotics (OR = 15.92, 95%CI = 3.57-70.94, P < .001). Conclusion: Two major adjustable factors for preventing diaper dermatitis in the study population were toilet training before 2 years of age and avoiding the use of unnecessary oral antibiotics. These results may help in devising a preventive protocol for diaper dermatitis among this age group in the future.